Students’ Perception on Online Learning of English Grammar Course: Determining the Challenges Faced by The Students - Fatma Patadjenu; Elsje Louise Sambouw; Muzdalifah Mahmud (Research Review: Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this research is to elaborate on students' perceptions of online learning in the English grammar course, Department of English, State University of Gorontalo. The participants in this study were 15 students from all classes for the 2020/2021 academic year, 3 of whom were taken from each class. This study uses qualitative research method, the data obtained from the results of written interviews. Next, this this study uses thematic analysis to analyze the data. The results of this study found 6 themes consisting of implementing online classes, advantages of online classes, disadvantages of online classes, constraints on using online classes, independent learning, and suggestions. Online learning has been implemented since the Covid¬19 pandemic. And this raises various perceptions from students regarding online learning itself. This is evidenced by the perceptions of students who have been given to this research. Then this online learning has positive and negative impacts. In other words, online learning has advantages and disadvantages. Furthermore, the results of this study indicate that most students strongly disagree if online learning can be used on an ongoing basis. Considered the disadvantages and obstacles are more than the advantages.